WTAP Is Correlated With Unfavorable Prognosis, Tumor Cell Proliferation, and Immune Infiltration in Hepatocellular Carcinoma - Liang, Linjun; Xu, Hongfa; Dong, Qichao; Qiu, Lige; Lu, Ligong; Yang, Qing; Zhao, Wei; Li, Yong (Frontiers in Oncology, 2022)
WTAP is involved in various pathological and physiological processes, but its function in hepatocellular carcinoma (HCC) remains elusive. In this study, we investigated the role of WTAP in HCC. Firstly, the mRNA and protein of WTAP were expressed highly in HCC tissue, which reflected clinicopathological characteristics of HCC patients. Then, an interactive analysis of genetic profiles and Kaplan–Meier curves was performed to show that WTAP was an independent predictor of survival of HCC patients. Meanwhile, genes co-expressed with WTAP, potential protein–protein interactions, related signaling pathways, and immune cell infiltration were identified. It was found that high WTAP expression correlated with enhanced interactions between cytokines and their receptors, cell cycle, and chemokine signaling pathways, as well as increased immune cell infiltration. At last, WTAP knockdown experiments in vitro indicate that the WTAP silencing inhibited HCC proliferation and aggressiveness. We conclude that WTAP may be a novel biomarker for prognosis and a therapeutic target for HCC.